Legal Cooperation in the ASEAN Maritime Environment in the Free Trade Era: Its Implication for Indonesia - Idris Idris; Arfin Sudirman; Mursal Maulana; Amanda Yola (Hasanuddin Law Review, 2022)
For the past 30 years, an estimated 50 percent of the coral reef population has declined as a result of overfishing, pollution, coastal development, and climate change. Such decline risks jeopardizing livelihoods and the capacity for disaster risk reduction, as well as endangering marine biodiversity. With the emergence of free trade and the high mobility of modern ships, trade goods all over the world are increasingly affected by marine pollution. Since 1992, at least 600,000 tons of oil have entered the oceans each year, primarily from normal shipping operations, accidents, and illegal discharges, which contribute to more pollution than does offshore oil and gas exploitation. Recognizing the differentiation of circumstances in each maritime area, current international law, including that in Southeast Asia, regulates the framework of marine environment protection in cooperation with other states and other international organizations. Unfortunately, because the Association of Southeast Asian Nations framework does wield binding power, its declarations have yet to create significant improvements to the region’s marine environment. This paper discusses the urgency to create a new binding regulation within Association of Southeast Asian Nations that would obligate its Member States to actively protect the region’s marine environment.